Bailey & Love's short practice of surgery 2026-02-15T17:19:50+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Bulstrode, C. J. K; Russell, R. C. G; Williams, Norman S., 1947- (Arnold, 2000)

(untitled)
This edition offers information on trauma, orthopaedic surgery, plastic surgery, neurosurgery and maxillofacial surgery. Chapters have been added to include the role of radiology in surgical practice, surgical ethics among others